Exploring the Types of Teachers’ Questioning Strategies Used in EFL Secondary School Classroom - Putri, Vivien Pandu Wicara; Trisanti, Novia (Journal of English Language and Education, 2025)
Questioning strategies are a significant way for EFL teachers to encourage student’s participation and interaction in learning a language, particularly at the secondary level. This research examined the types and applications of questioning strategies used by a seventh-grade English teacher in an EFL classroom at MTs NU Mranggen in Central Java, Indonesia. A qualitative case study methodology gathered video-recorded lessons and teacher interviews, and analysed thematically. The study outcomes revealed that teachers used four types of strategies—prompting (14), probing (7), repetition (3) and redirecting (1)—with prompting dominant across lesson stages. The prompting strategy was often employed because it increases students' thought processes and improves critical thinking. The teacher employed these strategies at the lesson's opening, main, and closing activities. Educators and researchers can use the insights to improve their approaches and establish a dynamic learning environment.